Stroke Epidemiology in an Australian Rural Cohort (SEARCH). Issue 2 (February 2017) - Newbury, Jonathan; Kleinig, Tim; Leyden, James; Arima, Hisatomi; Castle, Sally; Cranefield, Jennifer; Paterson, Tracey; Jannes, Jim; Crotty, Maria; Anderson, Craig S
Background: Stroke rates in Australia and New Zealand have been declining since 1990 but all studies have been completed in large urban centers. Aim: We report the first Australasian stroke incidence study in a rural population. Methods: The authors applied the principle of complete ascertainment, used the WHO standard definition of stroke and classified ischemic stroke by the TOAST criteria. Data were collected from five rural centers defined by postcode of residence, over a 2-year period with 12 months of follow up of all cases. Results: There were 217 strokes in 215 individuals in a population of 96, 036 people, over 2 years, giving a crude attack rate of 113 per 100, 000 per year. The 181 first-ever strokes (83% of total), standardized to the WHO world population, occurred at a rate of 50/100, 000 (95% CI: 43–58). The 28-day fatality for first-ever strokes was 24% (95% CI: 18–31) and 77% (95% CI: 71–83) were classified as ischemic (140/181), 15% (95% CI: 10–21) intracerebral hemorrhage, 3% (95% CI: 1–6) due to subarachnoid hemorrhage and 5% (95% CI: 2–9) were unknown. A high proportion of first-ever ischemic strokes (44%) were cardioembolic, mostly (77%) due to atrial arrhythmias. Of the 38 with known atrial arrhythmias prior to stroke, only six (16%) were therapeutically anticoagulated. Conclusions: This rural companion study of a recent Australian urban stroke incidence study confirms the downward trend of stroke incidence in Australia, and reiterates that inadequate anticoagulation of atrial arrhythmia remains a preventable cause of ischemic stroke.